UPAYA PENINGKATAN KEMAMPUAN MENULIS KARANGAN EKSPOSISI SISWA MELALUI MEDIA GAMBAR BERSERI PADA MATA PELAJARAN BAHASA INDONESIA KELAS III MI MUHAMMADIYAH KALIMANDI - Nur Innayah Ganjarjati; Kharis Kharis; Drajat Wahyu Lestari (Jurnal Ilmiah Ibtida: Jurnal Prodi PGMI STIT Pemalang, 2022)
This research was carried out with the aim of improving student’s writing by using picture series media for third grade students of MI Muhammadiyah Kalimandi, for the academic year 2021/2022. This type of the research includes classroom action research, which is carried out in two cycles. The research subjects were students of class III MI Muhammadiyah Kalimandi, with 9 students. The research design used is a cyclical design with a spiral model developed by Kemmis and MC. Taggart. The research methods used include: interviews, tests, observations, documentation. Descriptive statistical data analysis technique is to find the mean. The results of this study indicate that the use of serial image media can improve writing skills of third grade students of MI Muhammadiyah Kalimandi. This increase is indicated by the average score of students in the pre-action by 35.5, increasing to 54.4 in the first cycle and in the second cycle increasing to 77.7.